Die Mar̈kte fur̈ Schlachtvieh und Fleisch - Friedrich-Wilhelm Probst (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– (5) Based on estimated head numbers world bovine meat production is expected to show a slight dent in 2001 but any prognosis of developments in the world beef market crucially depends on the outcome of regional difficulties as e.g. animal diseases or economic crises. Following the detection of growing numbers of BSE-infected animals in several continental member states the EU beef and cattle markets are at present badly affected by a new scare. Prices reflect a steep fall of consumer confidence and governments hastened to demonstrate activities in trying to eradicate the dangerous disease. Meat and bone meals were totally banned from animal feeding rations and destruction of some two million untested carcasses is envisaged. World pig meat production is on the whole rising while EU production may show a 1 % reduction. However, EU prices, demand and net trade will strongly depend on developments in the beef market.
Keywords: 330